Teachers' Perceptions of Using Computers - Hend Abdullah Bamalan (Journal of Arts, Literature, Humanities and Social Sciences, 2025)
This study investigated teachers' perceptions of using computers in their classrooms. The study used secondary data from the Fast Response Survey System (FRSS): Teachers’ use of educational technology in U.S. public schools by the United States Department of Education, Institute of Education Sciences, and National Center for Education Statistics. The survey was conducted from 2008-2009. The study used a chi-square statistical test and analysis of variance (ANOVA test) to examine the research questions. Three results emerged from the study. First, the results showed a connection between how teachers and their students utilized computers during classroom instruction and the teachers' years of experience in elementary or secondary education. Secondly, no correlation was found between the usage of computers by teachers or their students during instructional time and the type of community. Lastly, the third result highlighted a variation in the number of internet-connected computers introduced to schools, depending on the community type. The findings demonstrate a significant relationship between teachers' years of experience and students' engagement with computers during instructional time. This indicates that more experienced educators may utilize technology differently than their less experienced counterparts. Conversely, the lack of a relationship between computer usage and community type suggests widespread access to technology across various settings. However, the effective integration of such resources may still vary based on individual teaching practices rather than environmental factors. The study recommended studying how teachers and students interact while using computers during lessons and how this affects students' academic success. In addition, studies could compare students’ success based on the types of training teachers receive.